Distribusi Zakat Mal Berbasis Al-'Adl dalam Meningkatkan Kesejahteraan Mustahiq (Studi Laznas Baitul Mal Hidayatullah Sulawesi Selatan) - Jamaluddin Uddin; Irwan Misbach; Abdul Wahab (Al-Ulum, 2020)
The main problem of this research is how is the distribution of zakat mal based on al-‘adl in improving the welfare of mustahiq at LAZNAS BMH South Sulawesi? This type of research is classified as qualitative with the research approach used is: theological-normative and sociological economics. The results of this study indicate that the distribution of zakat mal conducted by LAZNAS BMH South Sulawesi, there are two patterns, namely: consumptive distribution patterns and productive distribution patterns. The consumptive pattern of zakat mal is given to meet the basic needs of mustahiq, while the productive pattern is given in the form of empowering Human Resources, which is formidable preachers, poor education scholarships, empowered boarding school economics, and social community programs. Distribution of zakat is done by applying the values ​​of justice namely; proportional justice, not tyrannical, and recognizing freedom, the distribution process always embarrasses the scale of priorities that mustahiq most need.